THE LEGAL REGULATION OF DRUGS AS OBJECTS OF PATENTED PROTECTION - Yuliya Aleksandrovna Titenko; Irina Mikhailovna Vilgonenko; Lyudmila Konstantinovna Sukhacheva (Современная наука и инновации)
In article types of the medicines which are subject to protection by means of patent law are defined and also the research of features of legal regulation concerning different types of medicines is conducted. The problems arising in the course of regulation of separate types of medicines are allocated. Need of further improvement of legal regulation of separate types of medicines is proved.